The influence of Abiotic factors on the occurrence of jackfruit dieback disease - Idris, Nurul Hawani; Mohd Hata, Erneeza; Adnan, Norliza; Teri, Sazlieya Saupi; Osman, Mohamad Jahidi; Md Din, Ami Hassan; Ishak, Mohamad Hafis Izran (Universiti Putra Malaysia, 2023)
The jackfruit (Artocarpus heterophyllus) is one of six high-value non-seasonal tropical fruits identified as a target for export fruit products in the Malaysia National Key Economic Area (NKEA) report. It is challenging to sustain the jackfruit crop’s productivity and achieve the targets for the growth of premium fruits because of the emergence of plant diseases that can affect yields. This paper discusses the influence of abiotic factors, including landscape and weather, on the occurrence of Erwinia carotovora disease. This paper applied Ordinary Least Square (OLS) and hotspot analysis to understand the occurrence of the disease from the landscape and spatial perspective. The findings suggest that the rate of E. carotovora in jackfruit trees (based on a percentage of the area affected) is significantly affected by the proximity of the trees to roads, rivers, and irrigation. At the same time, the frequency of E. carotovora is substantially dependent on rainfall levels. The Koenker (BP) statistic provides a consistent set of results that explain the relationship between variables that impact the occurrence of dieback jackfruit disease remains the same over the study area. This study helps us understand how specific landscape characteristics and climatic variables influence jackfruit dieback disease. This area of research is essential so that the best land management practices can be adapted to prevent future disease occurrences.